Revised diagnoses of Hadrosaurus foulkii Leidy, 1858 (the type genus and species of Hadrosauridae Cope, 1869) and Claosaurus agilis Marsh, 1872 (Dinosauria: Ornithopoda) from the Late Cretaceous of North America - Prieto-Márquez, Albert (Zootaxa, 2011)
Hadrosauridae constitutes a very diverse clade of herbivorous dinosaurs that were extremely abundant during the Campanian–Maastrichtian (Late Cretaceous) of Europe, Asia, both Americas, and probably also Antarctica (Horner et al. 2004). The fact that hadrosaurids are one of the best-known clades of dinosaurs, represented by arguably the richest dinosaurian fossil record, contrasts with the scarcity of material and apparently undiagnostic nature of their type genus and species, Hadrosaurus foulkii. The holotype and only known specimen of H. foulkii is also historically significant for being the first skeletal remains of a dinosaur described outside Europe (Leidy 1858).